Wi-Fi Sensing for Indoor Localization via Channel State Information: A Survey - Suroso, Dwi Joko; Adiyatma, Farid Yuli Martin; Cherntanomwong, Panarat (Faculty of Engineering, Universitas Tanjungpura, 2023)
Wireless Fidelity (Wi-Fi) sensing utilization has been widespread, especially for human behavior/activity recognition. It provides high flexibility since it does not require the person/object to carry any device known as device-free. This